A Pilot Nurse-Led Tele-Counseling Intervention to Parents of Children With Cerebral Visual Impairment on Adherence to Eye Activities During COVID-19 Pandemic: A Pre-experimental Study - Dhiman, Sonam; Saini, Sushma Kumari; Chaurasia, Shweta; Duggal, Mona; Miglani, Vaibhav; Raj, Srishti (Frontiers in Medicine, 2022)
Aim: To assess the impact of culturally appropriate and theoretically driven nurse-led tele-counselling intervention to parents of children with Cerebral visual impairment (CVI) on adherence to visual-therapy advised by the ophthalmologists. Design: A pre-experimental design was used. Methods: Parents of children CVI age 2 to 9 years were enrolled telephonically during COVID-19 pandemic through Pediatric Ophthalmology Clinic of a tertiary eye care centre. Pre-assessment of participants was done telephonically as per interview schedule. As per the protocol, the trained nurse delivered tele-counselling intervention twice weekly for first 2 weeks and once weekly for next 2 weeks via audio and video two-way tele-interaction with parents. A CVI information booklet was shared with parents via whatsApp interface and individualized visual-therapy was re-inforced in accordance with the advice of the treating ophthalmologist after a thorough review of clinical records of child including CVI questionnaire, history, and findings of clinical examination including neuro-visual behaviour of child. In addition, parents were encouraged to maintain a diary of daily sessions of visual therapy and share recorded videos of their training exercises which were evaluated and discussed with the ophthalmologist for any deviation. Outcome measures included adherence to eye activities for 7-8 sessions per day. Data was analyzed by using SPSS statistics for windows, version 20. Results: Improvement of adherence to eye activities was observed among children with CVI (P<0.0001). Nearly half (47.6%) of participants were adherent to 3-4 sessions/day and only 28.6% were adherent to recommended 7-8 sessions/day. Conclusion: The pilot study demonstrated the potential of the nurse-led tele-counselling intervention to supplement the patients' ongoing health treatment in improving the adherence to eye activities among parents of children with CVI.